Vulnerability of artisanal fisheries to climate change in the Venice Lagoona. Issue 4 (31st May 2013) - Pranovi, F.; Caccin, A.; Franzoi, P.; Malavasi, S.; Zucchetta, M.; Torricelli, P.
<x xml:space="preserve">Abstract</x> Within the context of global warming, the western coast of the northern Adriatic Sea can be regarded as an extremely vulnerable area. Owing to the local geographic features, this area has been described as the Venetian lacuna, where Mediterranean Sea climatic conditions are replaced by Atlantic Ocean ones, supporting the presence of glacial relicts, such as sprat Sprattus sprattus, flounder Platichthys flesus and brown shrimp Crangon crangon. Nektonic assemblage therefore represents a good candidate in terms of an early proxy for thermal regime alterations. It represents a dynamic component of the lagoon ecosystem, changing in space and time, actively moving through the entire system, and dynamically exchanging with the open sea. Here, the first signals of the change have been already detected, such as the presence of alien thermophilic species. Within this context, since the beginning of the century, sampling of the nektonic assemblage has been carried out, integrating them with landings data from the fish market. Vulnerabilities to thermal regime changes have been tested by (1) categorizing species according to the mean distribution area in terms of latitudinal range (over 45°, 30°–45° and below 30°), and (2) analysing both spatial and temporal variations within fishing grounds. Results indicated a high potential vulnerability of the artisanal fishery to climate change, as the commercial catch is entirely composed of species from cold (>45° N) and temperate (between 45° and 30° N) latitudes. At present no alien thermophilic species have been recorded within the lagoon, which is possibly a sign of good resilience of the assemblage. Finally, abundance of species from cold latitudes has decreased during the past decade. All of this has been discussed in the context of the mean annual temperature trend.